1977
DOI: 10.1055/s-0028-1093496
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Exogenous Insulin to Inhibit Insulin Secretion in Man

Abstract: In order to explore whether or not the negative feedback mechanism of insulin per se on insulin secretion exists in man, changes in plasma C-peptide immunoreactivity (CPR), as an index of pancreatic B cells secretory function, were studied in 6 nonobese healthy volunteers in the presence of high circulating levels of exogenous insulin. 10% glucose was infused concurrently so as to maintain blood sugar at the basal level. The insulin-glucose infusion was maintained for 120 minutes, achieving mean plasma levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1
1

Year Published

1980
1980
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 6 publications
1
13
1
1
Order By: Relevance
“…Apart from the question of positive feedback, there was no suppressive effect of exogenous insulin on CPR release in the perfused rat pancreas, to say the least. This is in essential agreement with the finding in our previous work on man (Shima et al, 1977) which demonstrated the inability of exogenous insulin to inhibit the secretory function of the B cell in the basal state. The conclusion we reached disagrees with that of Liljenquist et al (1978) who used a similar method.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Apart from the question of positive feedback, there was no suppressive effect of exogenous insulin on CPR release in the perfused rat pancreas, to say the least. This is in essential agreement with the finding in our previous work on man (Shima et al, 1977) which demonstrated the inability of exogenous insulin to inhibit the secretory function of the B cell in the basal state. The conclusion we reached disagrees with that of Liljenquist et al (1978) who used a similar method.…”
Section: Discussionsupporting
confidence: 82%
“…The conclusion we reached disagrees with that of Liljenquist et al (1978) who used a similar method. In their study a much larger amount of insulin was administered for a longer period than in our previous in vivo study (Shima et al, 1977). In the present experiment we utilized the same amount as in the experiment of Loreti et al (1974) who used the largest amount of rat insulin ever employed in such experiments.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Exogenous hyperinsulinaemia also presents the potential problem that insulin has been shown to have an inhibitory effect on its own secretion in vitro. Existing data as to whether this is significant in vivo is conflicting, with inhibition being found in some studies, but not in others [23][24][25][26]. While an inhibitory effect may lead to an underestimation of the secretory responses, the same insulin infusion rates were used in both the placebo and treatment arms in the current study and so would not be expected to affect the comparison between them.…”
Section: Discussionmentioning
confidence: 97%
“…Much work has been published supporting (Elahi et al, 1982;lijenquist et al, 1978;Beischer et al 1978;Greenfield et al, 1981;DeFronozo et al, 1981) and arguing against (Ohagawara et al, 1973;Shima et al, 1977;Sando et al, 1970) the possibility of feedback inhibition of endogenous insulin secretion by exogenous insulin.…”
mentioning
confidence: 99%